Sex tourism : marginal people and liminalities - Ryan, Chris (Routledge, 2015)
Sex Tourism examines the issues which emerge from sex worker-client interactions and from tourists visiting 'sex destinations'. It is a comprehensive summary of past research by academics and original research by the authors.